2019
DOI: 10.1124/jpet.119.258004
|View full text |Cite
|
Sign up to set email alerts
|

Non-Opioid Neurotransmitter Systems that Contribute to the Opioid Withdrawal Syndrome: A Review of Preclinical and Human Evidence

Abstract: Opioid misuse and abuse is a major international public health issue. Opioid use disorder (OUD) is largely maintained by a desire to suppress aversive opioid withdrawal symptoms. Opioid withdrawal in patients seeking abstinence from illicit or prescribed opioids is often managed by provision of a m-opioid agonist/partial agonist in combination with concomitant medications. Concomitant medications are administered based on their ability to treat specific symptoms rather than a mechanistic understanding of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 171 publications
2
40
0
Order By: Relevance
“…For ease of interpretation, withdrawal symptoms are presented in categories that represent the following general domains: anxiety/escape behaviors (digging, jumping, rearing, and escape attempts), body temperature (measured in ºC, teeth chattering), gastrointestinal symptoms (diarrhea, defecation), hyperactivity (chewing, grooming, foot licking, genital licking), pain/hyperalgesia/ ptosis (writhing), and tremors/shaking (body, head shakes). These categories are based on meaningful clusters that have been identified within the human clinical literature (Dunn et al, 2019). Withdrawal severity (operationalized as number of presentations within each 10-minute scoring period) and total score (operationalized as total number of symptoms with >1 incidence during each 10-minute scoring period), as well as the physiological rating of body temperature were evaluated using separate repeated measures one-way ANOVA, with time as a within-subject repeated measure.…”
Section: Methodsmentioning
confidence: 99%
“…For ease of interpretation, withdrawal symptoms are presented in categories that represent the following general domains: anxiety/escape behaviors (digging, jumping, rearing, and escape attempts), body temperature (measured in ºC, teeth chattering), gastrointestinal symptoms (diarrhea, defecation), hyperactivity (chewing, grooming, foot licking, genital licking), pain/hyperalgesia/ ptosis (writhing), and tremors/shaking (body, head shakes). These categories are based on meaningful clusters that have been identified within the human clinical literature (Dunn et al, 2019). Withdrawal severity (operationalized as number of presentations within each 10-minute scoring period) and total score (operationalized as total number of symptoms with >1 incidence during each 10-minute scoring period), as well as the physiological rating of body temperature were evaluated using separate repeated measures one-way ANOVA, with time as a within-subject repeated measure.…”
Section: Methodsmentioning
confidence: 99%
“…The opioid-sparing properties of cannabinoids were first acknowledged in 1889 [ 10 ], and are evident within preclinical studies that report high potency cannabinoids produce robust and meaningful shifts in opioid-induced analgesia [ 11 , 12 ]. Patient surveys [ 13 16 ] and epidemiological evidence reports that reductions in opioid-reliance and consequences following medicinal cannabis exposure [ 17 , 18 ] suggested these preclinical outcomes might generalize into human clinical samples, and this collective information was the basis upon which several states added OUD as a qualifying condition for medicinal cannabis prescribing [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] In addition to oxidative stress, there is a disruption of glutamate homeostasis during opioid withdrawal resulting in an increase in synaptic glutamate (excitatory neurotransmitter) that leads to increased neuronal firing. [17][18][19][20][21] This increase in synaptic glutamate occurs because of decreased tone and function of the extrasynaptic metabotropic glutamate autoreceptors, mGluR2/3, which normally inhibits synaptic glutamate release (this decreased inhibition leads to increased synaptic glutamate) 17,20 and decreased function of glial glutamate transporter-1, which causes reduced glutamate elimination from extracellular space resulting in spillover of synaptic glutamate. 17,20 Ongoing research in both humans and animals are investigating restoring the glutamate and redox imbalance with N-acetylcysteine (NAC).…”
Section: Introductionmentioning
confidence: 99%
“…20,22 Research in adult rats suffering from morphine withdrawal has shown that mGluR2/3 agonists attenuate symptoms of opioid withdrawal. 21,23,24 Furthermore, extensive research in adults with substance use disorders, specifically nicotine, cocaine, and the opioid heroin, demonstrate that NAC reduces cravings and cue reactivity. 20,25 Currently, no known studies have investigated the effects of NAC on opioid withdrawal in neonates.…”
Section: Introductionmentioning
confidence: 99%